2015
DOI: 10.1053/j.ajkd.2015.04.051
|View full text |Cite
|
Sign up to set email alerts
|

Dental Health and Mortality in People With End-Stage Kidney Disease Treated With Hemodialysis: A Multinational Cohort Study

Abstract: In adults treated with hemodialysis, poorer dental health was associated with early death, whereas preventive dental health practices were associated with longer survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
53
0
6

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(69 citation statements)
references
References 32 publications
2
53
0
6
Order By: Relevance
“…If it is difficult to verify the effectiveness of interventional studies, prospective observational studies can be preferred as a suboptimal solution to strengthen the causal relationship. Accordingly, prospective observational studies, such as ORAL‐D study , that examine the relationship between PD‐related peritonitis and oral disease in addition to oral hygiene habits should be carried out in the future.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…If it is difficult to verify the effectiveness of interventional studies, prospective observational studies can be preferred as a suboptimal solution to strengthen the causal relationship. Accordingly, prospective observational studies, such as ORAL‐D study , that examine the relationship between PD‐related peritonitis and oral disease in addition to oral hygiene habits should be carried out in the future.…”
Section: Discussionmentioning
confidence: 99%
“…Patients who carried out oral hygiene at least twice a day had a marginally significantly (P = 0.10) lower risk of PD-related peritonitis than those who did not (HR 0.56 [95% CI, 0.28-1.12]). Conversely, there were no (8) significant differences in the risk of PD-related peritonitis between patients with or without the use of dental floss (HR 0.65 [95% CI, 0.24-1.50], P = 0.33) or between patients who last attended the dentist within 1 year or more than 1 year ago (HR 1.22 [95% CI, 0.61-2.45], P = 0.58). Consistent results were obtained even in the analysis using a Fine-Gray proportional hazards model (data not shown).…”
Section: Association Between Pd-related Peritonitis and Oral Hygiene mentioning
confidence: 97%
“…Furthermore, large epidemiological studies indicate that poor oral health could have an adverse effect on general health in people with reduced kidney function. For instance, periodontitis and tooth loss were demonstrated to be associated with higher mortality (Palmer et al, 2015; Ricardo et al, 2015). These problems related to periodontitis can have negative impacts on perceived general health and be reflected in deterioration in HRQoL measured by means of the SF‐36.…”
Section: Discussionmentioning
confidence: 99%
“…Individuals undergoing dialysis typically have very poor oral health, [136][137][138][139][140][141][142] and for those with long-term hemodialysis, periodontitis is associated with an increased mortality. 137,140,143 One study reported a higher periodontitis risk for older Japanese women with lower cystatin C-based estimated glomerular filtration rate (eGFR).…”
Section: Chronic Kidney Diseasementioning
confidence: 99%